Italian Adult Comics in Sweden in the 1980s and 1990s - Igor Tchehoff (Moderna Språk)
The object of this paper is to present and analyze the main features of the extensive publication of Italian adult comics in Sweden in the 1980s and 1990s. Bibliographic and quantitative research has been conducted in order to supplement the bibliography of the Italian literature in Sweden compiled by Schwartz (2013). The results allowed for the conclusion that comics constituted a very significant share of translated Italian literature of the period, and the importance of individual publishers was higher in this segment. Making use of key concepts of Bourdieu, it is shown that adult comics in Sweden were assigned low cultural value compared to Italy. After a brief comparison of the situation of adult comics in both countries, regarding the role of mediators and the issue of cultural legitimacy, it is argued that this cultural transfer eventually led to a clash that culminated with the Freedom of the Press trial against Pox magazine. For a number of reasons, adult comics in Sweden have never achieved a sufficient level of cultural legitimacy and have remained on the margins of the cultural scene. The difficulties faced by Italian adult comics in Sweden are illustrated by a brief analysis of the reception of An Author in Search of Six Characters by Milo Manara (1992).